Analysis Of The Influence Of Work Engagement And Psychological Capital On Organizational Citizenship Behavior Of Employees In Government-Owned Marine Logistics Company - Suriadi; Eva Yuniarti Utami; H. M. Anwar; Yusuf Ronny Edward; Musran Munizu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to determine whether psychological capital and work engagement have a substantial impact on organizational citizenship behavior. Employees from the marketing, human resources, and claims divisions made up the population in this study. 300 employees were employed as respondents for this study. In this investigation, sampling was done using accidental and non-probability approaches. The researcher performed confirmatory factor analysis (CFA) to evaluate the measuring device's construct validity. Multiple regression analysis methods were employed in this study. The automated SPSS program was utilized to compute regression in this investigation. According to the findings of the study, psychological capital (self-efficacy, optimism, hope, and resilience) and work engagement (vigor, devotion, and absorption) have a considerable impact on employees' organizational citizenship behavior. Five independent variables were shown to have a substantial impact on organizational citizenship behavior according to the findings of the minor hypothesis test, which examined the regression coefficient of the independent variable on the dependent variable. Self-efficacy, optimism, resilience, vigor, and absorption are the five independent variables. Hope and dedication are two more independent variables that do not significantly affect outcomes. All independent variables together have an overall influence of 45% on organizational citizenship behavior. Additionally, self-efficacy, optimism, hope, resilience, vigor, and absorption are the six independent factors that significantly influence the proportion of variation to organizational citizenship behavior.